Cognitive Linguistics and Computational Modeling. - Valenzuela, Javier (Textus, 2010)
The article presents information on a study which examined influential cognitive linguistics (CL) computational models. The CL principle of cognitive commitment requiring the coherence of accounts of language with what other disciplines relay about cognition is discussed. The advantages of using a well-designed computational model for theory building are highlighted. The relationship between connectionism and CL is also analyzed.